Effect of deletions in the α-globin gene on the phenotype severity of β-thalassemia. (4th March 2022) - Saha, Dipankar; Chowdhury, Prosanto Kr.; Panja, Amrita; Pal, Debashis; Nayek, Kaustav; Chakraborty, Gispati; Sharma, Prashant; Das, Reena; Basu, Surupa; Chatterjee, Raghunath; Basu, Anupam
Abstract: Thalassemia is the most common inherited hemoglobinopathy worldwide. Variation of clinical symptoms in this hemoglobinopathy entails differences in disease-onset and transfusion requirements. The aim of this study was to investigate the role of α-globin gene deletions in modulating the clinical heterogeneity of β-thalassemia (β-thal) syndromes. A total number 270 β-thal subjects were enrolled. Hematological parameters were recorded. β-Globin mutations were determined by amplified refractory mutation system-polymerase chain reaction (ARMS-PCR), gap-PCR and Sanger sequencing. α-Globin gene deletions were determined by multiplex PCR. Out of 270 β-thal subjects, 19 carried β + /β +, 74 had β 0 /β 0 and 177 had the β 0 /β + genotype. When we determined the severity of the different β-thal subjects in coinherited with the α gene deletion, it was revealed that, 84.2% β + /β + subjects carried a non severe phenotype and did not have an α gene deletion. Of the β 0 /β 0 individuals, 95.9% presented a severe phenotype, irrespective of α-globin gene deletions. In cases with the β 0 /β + genotype, 19.2% subjects also carried a deletion on the α gene. Of these, 61.8% presented a non severe phenotype and 38.2% were severely affected. Only in the β 0 /β + category did α gene deletions make a significant contribution ( p  < 0.001) toward alleviation of clinical severity. Therefore, it can be stated that α-globin gene deletions play a role in ameliorating the phenotype in patients with a β + /β 0 genotype.